KAPASITAS ANTI RADIKAL EKSTRAK ANTOSIANIN BUAH SALAM (SYZYGIUM POLYANTHUM [WIGHT.] WALP) SEGAR DENGAN VARIASI PROPORSI PELARUT - Setyaningrum Ariviani (Caraka Tani: Journal of Sustainable Agriculture, 2010)
Dark red colored salam (Syzygium polyanthum (Wight.) Walp) fruits was expected contain of anthocyanin compounds. Recent research results have shown that anthocyanins from edible fruits were effective antioxidants. Antioxidative properties of anthocyanins arise from their high reactivity as  hydrogen or electron donors, and from the ability of the polyphenol-derived radicals to stabilize and delocalize the unpaired electronn, and from their ability to chelate transition metal ion. This research aims to determine anti radical capacity of anthocyanin extract from fresh salam fruits extracted with different solvent proportion and their correlation to the total anthocyanin content. Results indicated anthocyanin extract from fresh salam fruits showed anti radical capacity that increased along to solvent proportion raised. The anti radical capacity showed high correlation with the total anthocyanin content (R 0.954, P<0.05).